2019
DOI: 10.1002/pssa.201900501
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Efficiency Enhancement of Bialkali Photocathodes by an Atomically Thin Layer on Substrates

Abstract: Quantum efficiency (QE) enhancement in accelerator technology relevant to antimonide photocathodes (K2CsSb) is achieved by interfacing them with atomically thin 2D crystal layers. The enhancement occurs in a reflection mode, when a 2D crystal is placed in between the photocathodes and optically reflective substrates. Specifically, the peak QE at 405 nm (3.1 eV) increases by a relative 10%, whereas the long wavelength response at 633 nm (2.0 eV) increases by a relative 36% on average and up to 80% at localized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…It suggests that the cathode is not properly formed. On the other hand, the result on Gra/Si of good quality graphene is consistent with a typical spectral response of CsK 2 Sb photocathode [2,[5][6][7]. The photocathode performance of the Gra/Si of good quality graphene was higher than that of Gra/Si of poor quality graphene.…”
Section: Qe Measurementsupporting
confidence: 84%
See 1 more Smart Citation
“…It suggests that the cathode is not properly formed. On the other hand, the result on Gra/Si of good quality graphene is consistent with a typical spectral response of CsK 2 Sb photocathode [2,[5][6][7]. The photocathode performance of the Gra/Si of good quality graphene was higher than that of Gra/Si of poor quality graphene.…”
Section: Qe Measurementsupporting
confidence: 84%
“…Generally, CsK 2 Sb photocathode is produced by depositing the cathode element on a substrate, so that the cathode performance strongly depends on the substrate material, including crystallinity1,4, surface state (contamination, roughness, and surface orientation) [1,[4][5][6] and dopant types [2]. If the substrate after cathode production is used again by heat cleaning, the performance of the reproduced cathode will drastically deteriorate.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have successfully demonstrated the compatibility of graphene and alkali antimonide (K 2 CsSb) photocathodes by directly depositing high-quality K 2 CsSb on both supported and suspended few-layer graphene. The K 2 CsSb deposited on graphene had good crystallinity, close to theoretical stoichiometry, and high QEs that were comparable to those deposited on conventional thick metal substrates, with the peak QE exceeding 14% at 3.1 eV on the graphene substrate. However, no photoemission through graphene was observed due to the possible polymer residue from the graphene transfer process and the limited instrument sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Our strategy to achieve this was to deposit thin metal films onto CsK 2 Sb photocathodes via thermal deposition from the opposite side of graphene protection layer. We had already established a protocol to fabricate CsK 2 Sb photocathodes on graphene protection layer [30][31][32][33][34] thus the remaining task was to select an appropriate sealing metal for our purpose. It is well known that substrate material has severe effects on the QE of deposited ~ 20 nm think CsK 2 Sb photocathodes 8 , therefore it was crucial for us to identify a metal with minimal degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Au was chosen for its chemical inertness, which could prevent photocathodes from interacting with corrosive gases such as oxygen and moisture. Ni was chosen for its potential material compatibility with CsK 2 Sb based on our prior studies [30][31][32][33][34] . We did not test molybdenum (Mo) despite its known material compatibility with CsK 2 Sb because of a concern on its high evaporation temperature.…”
Section: Resultsmentioning
confidence: 99%